Pengukuran Indeks Pembangunan Manusia (IPM) Kabupaten Bojonegoro Tahun 2024 - Patiung, Markus; Ernawati, Ernawati (Jayapangus Press, 2024)
The Human Development Index (HDI) is an important indicator for measuring the success of efforts to improve the quality of human life and serves as one of the indicators of development performance in a region. The objectives are (1) to provide input to the Bojonegoro Regency Government on the extent of achievements in the quality of life of its people and (2) to evaluate human development through efforts to improve the achievement of each indicator, including Life Expectancy, Expected Years of Schooling, Average Years of Schooling and per capita Purchasing Power of the people of Bojonegoro Regency. This research employs a mixed-method approach, combining both qualitative and quantitative research. Successful human development is characterized by providing opportunities for people to enjoy a long and healthy life and lead a productive life. The purchasing power of the community positively influences the increase in Clean and Healthy Living Behavior (PHBS), which in turn positively impacts the increase in Life Expectancy. Improvements in education can raise public awareness of the importance of Clean and Healthy Living Behavior. Thus, PHBS itself can mediate and strengthen purchasing power and average years of schooling, thereby influencing the increase in Life Expectancy. Conclusions (1) The HDI of Bojonegoro Regency from 2020 to 2023 experienced an average increase of 0.54 points. In 2023, the HDI was 71.80, with the achievement of each indicator as follows Life Expectancy was 74.72 Expected Years of Schooling was 12.92 Average Years of Schooling was 7.45 and per capita Purchasing Power was Rp. 10,776,000. (2) The projected HDI for 2024 is 72.53, an increase of 0.73 points, with the HDI indicators being Life Expectancy at 75.01, Expected Years of Schooling at 13.04, Average Years of Schooling at 7.51, and per capita Purchasing Power at Rp. 11,263,000.